Opioids and Injury Deaths: A population-based analysis of the United States from 2006 to 2017. Issue 8 (August 2021) - Truong, Evelyn I.; Kishawi, Sami K.; Ho, V.P.; Tadi, Roshan S.; Warner, David F.; Claridge, Jeffrey A.; Tseng, Esther S.
Highlights: We hypothesized that prescription opioid use would be positively associated with injury-related deaths in the US. For each state, we analyzed mortality data from the US CDC and prescription opioid data from the US department of justice from 2006–2017. There was no relationship between amounts of opioids and injury-related mortality, including unintentional deaths, suicides, and homicides. We did not find a direct association between prescription opioids and injury mortality despite the detrimental effects of the opioid epidemic. Abstract: Introduction: In the United States, the opioid epidemic claims over 130 lives per day due to overdoses. While the use of opioids in trauma patients has been well-described in the literature, it is unknown whether prescription opioid use is associated with mortality after trauma. We hypothesized that legally obtained prescription opioid consumption would be positively associated with injury-related deaths in the United States. Methods: Cross-sectional time-series data was compiled using state-level mortality data from the Centers for Disease Control and Prevention Multiple Causes of Death database and prescription opioid shipping data to each state using the US Department of Justice Automated Reports and Consolidated Ordering System Retail Drug Summary reports from 2006 to 2017, with opioids shipped used as a proxy for local opioid consumption. Oxycodone and hydrocodone amounts were converted to morphine equivalent doses (MEDs). Our primary outcome was an association between MEDs and injury mortality rates at the state-level. We analyzed total injury-related deaths and subgroups of unintentional deaths, suicides, and homicides. We modeled the data using fixed effects regression to reduce bias from unmeasured differences between states. Results: Data were available for all states and the District of Columbia. Opioid deliveries increased through 2012 and then declined. Total injury-related mortalities have been increasing steadily since 2012. Opioid MEDs did not show a consistent or statistically significant relationship with injury-related mortality, including with any subgroups of unintentional deaths, suicides, and homicides. Conclusion: In every state examined, there was no consistent relationship between the amount of prescription opioids delivered and total injury-related mortality or any subgroups, suggesting that there is not a direct association between prescription opioids and injury-related mortality. This is the first study to combine national mortality and opioid data to investigate the relationship between legally obtained opioids and injury-related mortality. The US opioid epidemic remains a significant challenge that requires ongoing attention from all stakeholders in our medical and public health systems.